1988
DOI: 10.1113/jphysiol.1988.sp016956
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐ and single‐fibre mesenteric and renal sympathetic responses to chemical stimulation of intestinal receptors in cats.

Abstract: SUMMARY1. In cats anaesthetized with a-chloralose and artificially respired, stimulation of intestinal receptors with bradykinin caused greater reflex excitation of mesenteric than of renal efferent multifibre nerve activity and significant pressor responses.2. Activity of all nerve bundles used in this study was inhibited by stimulation of pressoreceptors. Increases in systemic arterial pressure caused inhibition of activity of renal nerves which was significantly greater than that of mesenteric nerves.3. Spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 28 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…Such subpopulations of nerves have been demonstrated previously in the gut (13) and eye (3), although such a possibility in the kidney has received little attention until the last decade (8,9,11,15,39,40). It has generally been accepted that the stimulation of the renal nerves produces frequency-dependent decreases in renal function (see Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such subpopulations of nerves have been demonstrated previously in the gut (13) and eye (3), although such a possibility in the kidney has received little attention until the last decade (8,9,11,15,39,40). It has generally been accepted that the stimulation of the renal nerves produces frequency-dependent decreases in renal function (see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, we hypothesized that different patterns of sympathetic outflow to the kidney may evoke selective changes in segmental renal vascular resistances. This concept of functionally specific populations of renal sympathetic nerves has also been addressed by other investigators (8,9,11,15,39,40).…”
mentioning
confidence: 80%
“…This conclusion could not have been reached in microneurographic recordings of multiunit sympathetic bursts, which have been the standard approach to recording from postganglionic sympathetic fibres in human peripheral nerves. The maximum number observed within a burst was seven, which is also what Hallin & Torebjork (1974) (0 5-3 Hz;Jainig, 1985), as well as from renal, splenic and mesenteric nerves in the cat (0-03-6-4 Hz, median 0 9 Hz; Meckler & Weaver, 1988;Stein & Weaver, 1988). It should be noted, however, that our subjects had low levels of spontaneous multiunit activity (range 9-17 bursts min-').…”
Section: Latency Variationsmentioning
confidence: 92%
“…In the present material short interspike intervals, with instantaneous frequencies greater than 50 Hz, were produced by nine units, but only 2-4% of all intervals were so short. Single vasoconstrictor motoneurones in the renal, splenic and mesenteric nerves of the cat also generate high instantaneous firing rates, up to 59 Hz, and the frequency distribution is similarly broad (Meckler & Weaver, 1988;Stein & Weaver, 1988). Such erratic instantaneous frequencies may be physiologically appropriate; electrical stimulation of sympathetic nerves has shown that irregular interstimulus intervals are more effective than regular stimuli for contracting arterioles in the muscle vascular bed of the cat, the optimal pattern being a 32 Hz stimulus applied at 4 s intervals (Andersson, 1983).…”
Section: Latency Variationsmentioning
confidence: 99%
“…These include factors described in the dopamine /3-hydroxylase-deficient patients, since tetraplegics also have the ability to activate vagal efferent pathways and may release peptides and other vasoconstrictor active substances from sympathetic nerve endings. Studies in intact and spinalized animals suggest that viscerosympathetic reflexes may be organized so as to preferentially activate the nerves to the organ from which the reflex originates 34 ; whether this occurs in the tetraplegic patients on intestinal stimulation is but speculative at this stage.…”
Section: Tetraplegia With Complete Cervical Cord Transectionmentioning
confidence: 99%